The process of siltation of the Pilcomayo River endangers Paraguayan sovereignty (Legal journal - Research in Legal and Social Sciences, 2023)
The Pilcomayo River historically flowed into the Paraguay River, constituting the boundary between Argentina and Paraguay. This research describes how the phenomenon of siltation -deposition of sediments raising the bed- of the Pilcomayo River affects Paraguayan sovereignty. The type of research is documentary, the level of study is descriptive, it seeks to specify the properties of the variables analyzed, with a qualitative approach, non-experimental design, observing the phenomena as they occur in their natural context, without manipulating the variables. A working commission was created to address the problems faced by this natural resource. In this sense, it can be affirmed that the lack of water in the Paraguayan canal in the period 2014 to 2016 was due to the fact that the works of the national public bidding process were carried out at the wrong time in relation to the period of the cyclical floods from December to March of each year. In fact, it is necessary that the excavation works carried out by the contractors be more specific as regards the depth and dimensions of the cross section, so that the entry of the flow in the Paraguayan channel is the same as on the Argentinean side, especially considering that its waters constitute a State patrimony and thus jeopardize the exercise of sovereignty, as well as agricultural and livestock production, the ecosystem and the quality of life of the inhabitants of the area.
Keywords: Pilcomayo River; siltation; hydraulic management; sovereignty; public bidding; quality of life